(untitled) (Comprehensive Journal of Science, 2026)
This study, following an analytical approach, examines the legal provisions regulating old-age pensions in Libya as an integral part of the social security system, in accordance with Law No. (13) of 1980 and its implementing regulations. The study highlights the existence of legislative inconsistencies in determining the retirement age, due to the multiplicity of laws governing this matter. It also emphasizes that the current pension value may not provide a decent standard of living under the prevailing economic conditions. The study recommends unifying the legal retirement age and adjusting pension values to ensure the intended social protection.